Capsular polysaccharide of Streptococcus agalactiae is an essential virulence factor for infection in Nile tilapia (Oreochromis niloticus Linn.). Issue 2 (14th December 2018) - Zhang, Defeng; Ke, Xiaoli; Liu, Zhigang; Cao, Jianmeng; Su, Youlu; Lu, Maixin; Gao, Fengying; Wang, Miao; Yi, Mengmeng; Qin, Fengling
Abstract: Streptococcus agalactiae (Group B Streptococcus, GBS) is associated with diverse diseases in aquatic animals. The capsule polysaccharide (CPS) encoded by the cps gene cluster is the major virulence factor of S. agalactiae ; however, limited information is available regarding the pathogenic role of the CPS of serotype Ia piscine GBS strains in fish. Here, a non‐encapsulated mutant (Δ cps ) was constructed by insertional mutagenesis of the cps gene cluster. Mutant pathogenicity was evaluated in vitro based on the killing of whole blood from tilapia, in vivo infections, measuring mutant survival in tilapia spleen tissues and pathological analysis. Compared to wild‐type (WT) GBS strain, the Δ cps mutant had lower resistance to fresh tilapia whole blood in vitro ( p < 0.01), and more easily cleared in tilapia spleen tissue, and was highly attenuated in tilapia and zebrafish. Additionally, compared to the Δ cps mutant, numerous GBS strains and severe tissue necrosis were observed in the tilapia spleen tissue infected with WT strains. These results indicated that the CPS is essential for GBS pathogenicity and may serve as a target for attenuation in vaccine development. Gaining a better understanding of the role, the GBS pathogenicity in fish will provide insight into related pathogenesis and host–pathogen interactions.